Potential aspergillus niger strain for the production of phenolics from a novel source palm oil mill effluent - Jamal, Parveen; Zulkarnain, Mohamed Idris; Alam, Md Zahangir; Zainudin, Zaki; Al-Mamun, Abdullah (Journal of Pure and Applied Microbiology, 2014)
Palm oil mill effluent (POME) is one of the major sources of aquatic pollution in Malaysia. Phenolics production using organic residue of POME and potential Aspergillus niger strains would be a novel approach to solve this problem. Thus screening was conducted for seven locally isolated Aspergillus niger strains namely IBS-101ZA, IBO-103MNB, IBS-103ZA, IBS-104ZA, IBS-105ZA, IBS-106ZA and IBO-107MNB at 24, 48, 72, 96 and 120 hours of fermentation and at fixed process conditions of 150 rpm of agitation rate, 2% (v/v) of inoculum size, 4% (w/v) of solid concentration and at the temperature of 30 ? 2 ?C. The substrate was added with co-substrates of 2% (w/v) of wheat flour, 2% (w/v) of glucose and 2% (w/v) of ammonium nitrate to enhance the growth of the strains. The selection of the potential fungal strain was determined on the basis of growth rate and highest total phenolic content. No significant difference (p >0.05) in radial growth rates between Aspergillus niger strains was observed. The distribution of phenolic compounds produced by different Aspergillus niger strains showed that the highest total phenolic content was obtained by IBS-103ZA strain with 639.9?4.19 GAE mg/L after 72 hours of fermentation.